Prevalence and Determinant of Respiratory Symptoms Among Rice Mill Workers in Sokoto State, Northwest Nigeria (International Journal of Occupational Safety and Health, 2022)
Introduction: Rice milling provides a means of livelihood to many in Northwest Nigeria, but like any other profession, it is not without risk. Workers in rice mills are exposed to hazards which has deleterious effects on many systems in the body, one of these is the respiratory system. This study aimed to determine the prevalence and factors that are associated with respiratory problems among rice millers in Sokoto State, Northwest Nigeria.Methods: A cross-sectional study was conducted between June 2019 and July 2019. An interviewer-administered questionnaire was used to obtain responses from the participants.Results: A total of 398 workers participated in the study, and 230(57.8%) of them had at least one symptom of respiratory morbidity. Morning cough 184(46.2%) had the highest prevalence, followed by chest tightness 157(39.4%). Cigarette smoking, involvement in de-husking and paddy separation were factors that increase the likelihood of having respiratory symptoms among the workers.Conclusion: The prevalence of respiratory symptoms is high among rice mill workers, and the factors that were found to determine the presence of respiratory symptoms were cigarette smoking, and involvement in de-husking and paddy separation.